Hubungan Antara Peluang dan Keputusan Manusia - Arnah Ritongah; Riby Tamara (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Human decision-making often occurs under conditions of uncertainty, where understanding probabilities is essential for making informed choices. This study investigates how people perceive and apply probabilistic information in various decision-making contexts. A combination of quantitative and qualitative methods was used to analyze the decision patterns of 200 individuals from diverse backgrounds through scenarios involving uncertainty. The results show that most participants prefer relying on intuition or personal experience rather than using statistical reasoning. Several cognitive biases, such as ignoring probability, overestimating confidence, and relying on readily available information, were commonly observed. However, participants with a stronger grasp of probability concepts demonstrated more logical and beneficial decision-making, particularly in financial and organizational settings. The study highlights a clear link between probability literacy and decision quality. Improving public understanding of probabilistic thinking could enhance decision outcomes, especially in situations involving risk. Educational efforts to integrate probability awareness into learning environments are recommended to support better decision-making both individually and collectively.